Odnos negovalnega tima do procesa zdravstvene nege v Splošni bolnišnici "Dr. Franc Derganc" Nova Gorica - Kalin Vodopivec, Monika (Obzornik zdravstvene nege, 2000)
The process of nursing care enables the systematic approach to the client and the solution of nursing problems. The goals of the introduction of this methodin health institutions is continuous nursing care of high quality. The present review article analyses the attitude of the nursing team towards the process of nursing care in the General Hospatal Dr. Franc Derganc in Nova Gorica. The aim of the research is to find out the opinion of nurses and nursing technicians about the implementation of the process of nursing care inthe treatment process of a patient/client. The study revealed that the carrying out of nursing according to the principles of the process of nursing care can be problematic which is in the first place the result of the age and the length of working period of the nurses. Personal changes, apathy and burn out are the reasons for alienated attitude towards new knowledge and progress in nursing care.
Keywords: bolnišnice; Hospitals, general; Job description; medicinske sestre; Nursing process; Nursing, team; Patient care team; Questionnaires; Workplace; zdravstvena nega